2004
DOI: 10.1111/j.1365-2222.2004.01839.x
|View full text |Cite
|
Sign up to set email alerts
|

An association study of asthma and total serum immunoglobin E levels for Toll‐like receptor polymorphisms in a Japanese population

Abstract: Our results indicate that polymorphisms in TLRs are not likely to be associated with the development of atopy-related phenotypes in a Japanese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
122
3
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(140 citation statements)
references
References 35 publications
10
122
3
4
Order By: Relevance
“…In line with this finding, induction of IL-8, a cytokine upregulated in response to TLR2 triggering, was also reduced in carriers of the TLR2 -196 to -174 del allele. Thus, our findings confirm that differential in vitro trans-activation of TLR2 promoter constructs as shown by Noguchi et al 10 corresponds to functional differences, when cells from patients carrying different TLR2 22bp del/ins variants are stimulated. Taken together, these findings support the concept that reduced TLR2 signaling leads to less effective immune responses facilitating viral replication with increased HCV counts in the serum.…”
Section: Short Reportsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with this finding, induction of IL-8, a cytokine upregulated in response to TLR2 triggering, was also reduced in carriers of the TLR2 -196 to -174 del allele. Thus, our findings confirm that differential in vitro trans-activation of TLR2 promoter constructs as shown by Noguchi et al 10 corresponds to functional differences, when cells from patients carrying different TLR2 22bp del/ins variants are stimulated. Taken together, these findings support the concept that reduced TLR2 signaling leads to less effective immune responses facilitating viral replication with increased HCV counts in the serum.…”
Section: Short Reportsupporting
confidence: 90%
“…10 To check, if this polymorphism affects TLR2 expression on immune-competent cells, we performed in vitro stimulation experiments with PGN and HCV-NS3, which upregulate TLR2 expression on monocytes and macrophages. These experiments clearly indicated impaired upregulation of TLR2 to be associated with the TLR2 -196 to -174 del allele.…”
Section: Short Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Moreover, in Asian populations, no functional TLR4 polymorphisms related to asthma have yet been discovered. [17][18][19][20] Given that the bakery workplace is characterized by both endotoxin and allergen exposure, we investigated the association of TLR4 polymorphisms with work-related respiratory symptoms and sensitization to flour allergens to further clarify the role of TLR4 in the development of baker's asthma. In a Korean population, we detected no known nonsynonymous single nuclear polymorphism (SNP) such as G299/I399.…”
Section: Introductionmentioning
confidence: 99%
“…We selected potentially functional polymorphisms À688G>T and c. À196 to À174 ins>del to evaluate the influence of genetic susceptibility on risk of GC, and found a significant association between TLR2 c. À196 to À174 ins>del and GC risk. A study in vitro has revealed that TLR2 c. À196 to À174 ins>del variant has a reduced transcriptional activity (40). Another study has also shown that H. pylori-infected patients with TLR2 c. À196 to À 174 del genotype had lower risk of developing dyspeptic symptoms, suggesting that this polymorphism may modify H. pylori-related inflammatory response and outcome of H. pylori infection (41,42).…”
Section: Discussionmentioning
confidence: 97%